Airway Scope for emergency intubations: usefulness of a new video-laryngoscope - Sadamori, Takuma; Kusunoki, Shinji; Otani, Tadatsugu; Ishida, Makoto; Masuda, Rieko; Tamura, Tomoko; Takeda, Taku; Tsumura, Ryu; Shokawa, Tomoki; Kondo, Tomohiro; Sakai, Hiroshi; Iwasaki, Yasumasa; et al. (Hiroshima journal of medical sciences, 2008)
The Airway Scope (AWS-S100, Pentax, Tokyo, Japan) is a new video-laryngoscope, which has a specially designed blade and a portable, battery-powered, 2.4-inch built-in liquid crystal device (LCD) full-color video screen at the top of the handle. In this study, we tested the usefulness of the AWS for tracheal intubation in acute, urgent situations. Patients admitted to the Advanced Emergency and Critical Care Center at Hiroshima University Hospital and who required orotracheal intubations were prospectively enrolled. Tracheal intubations were performed using the AWS by residents (the novice group) or staff physicians (the experienced group), who received a brief instruction in the AWS. We enrolled 38 patients (23 males, 15 females; age, 60 +/- 19 years). Intubations were attempted by 22 intubators (11 residents and 11 experienced personnel). The durations from inserting the blade via the oral cavity until observing the glottis (T1), inserting the tube into the trachea (T2), and confirming the chest rise (T3) were 22 +/- 15, 34 +/- 21 and 49 +/- 27 sec, respectively. When the results were classified into t experienced and novice groups, T1, T2 and T3 were 17 +/- 10 vs. 26 +/- 17, 32 +/- 23 vs. 36 +/- 20, and 45 +/- 25 vs. 53 +/- 27 sec, respectively (the experienced vs. the novice group, n.s.). These results suggested that the AWS may be a suitable device particularly for less experienced personnel, such as novice Advanced Life Support providers.